Simultaneous Intussusception in Monozygotic Twins - Mete Kaya; Serpil Sancar; Esra Özçakır (Güncel Pediatri, 2014)
In this case report, it was aimed to present the simultaneously occurring intussusception in the monozygotic twins. In addition to genetic predisposition, environmental factors has been hypothesized to be responsible for the development of the disease.